Peran Mise en scene Memvisualisasikan Sensualitas Tokoh Utama pada Film Charlie's Angels Rilis Tahun 2000: Analisis Male Gaze - Mochtar, Muhammad Gilang Maulana; Astuti , Soekma Yeni; Suprapto , Deddy (Universitas Jember, 2025)
Charlie’s Angels is an action comedy film released in 2000. The film tells the story of three beautiful women or called Angels (Natalie, Dylan and Alex) working in a private detective agency by highlighting very strong sensuality. Sensual visualization caused by the lewd environment and the choice of Angels’ clothing shows a connection between mise en scene and the male gaze. Cinematic visualization influences the interpretation of sensuality in the film and what happens in the film. This study uses Bordwell’s mise en scene theory in examining the sensuality of the male gaze to understand the conception of mise en scene by integrating the structure of three levels of the male gaze. Dividing the form of sensuality based on voyeurism, scopophilia and narcissism, the visualization of the Angels’ characters can be more visible in each scene. The research was conducted descriptively qualitatively with data collection techniques through the stages of observation, documentation, and literature study. Data obtained from observation were then reduced. Scenes that show the sensuality of the Angels characters became the limitations of the study. 6 scenes were obtained that were considered to have a major influence in the depiction of mise en scene and showed forms of sensuality based on three aspects of recognizing the male gaze: voyeurism, scopophilia and narcissism. Sensuality is seen through mise en scene with four aspects: setting, costume and make up, lighting and movement of the actor who is able to provide a visual form in the development of sensuality experienced by the Angels characters. Mise en scene is able to influence the sensuality of the male gaze in the film Charlie's Angels (2000) which uses women as sexy objects and erotic objects for visual purposes in the movie.